FAKT the Association for Appropriate Technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
FAKT is a non-profit consuitanay which was founded in 1986 by organizations of the Protestant Church in Germany to make technical expertise available to overseas partners. it also works on behalf of governmental organizations such as the German...